Studies on cryopreservation of cauda epididymal spermatozoa buffaloes - HARSHAN, HIRON M; SINGH, L P (The Indian Journal of Animal Reproduction, 2023)
The effect of cryopreservation on the viability, motility, acrosomal integrity, cervical mucus penetration ability andresponse to hypo-osmotic solution was studied on samples of cauda epididymal semen collected from 12 mature buffalo bullsslaughtered at the local slaughter house. Though a significant reduction (P
Keywords: Buffalo; cauda epididymal spermatozoa; cryopreservation